Effects of stocking density on the growth rate of gold fish fry reared in hapa - Shajib, Md Saroar Hossain; Sarker, Baadruzzoha; Asif, Abdulla Al; Rahman, Md Mizanur; Zafar, Md Abu; Hossain, Amir (Asian Journal of Medical and Biological Research, 2018)
The present study was conducted to investigate effects of stocking density on growth performances of gold fish (Carassius auratus) in hapas. Experiment was conducted for a month with three treatments where three stocking densities were T1 (10 fry/hapa), T2 (15 fry/hapa) andT3 (20 fry/hapa) each having three replications which were selected randomly. In the present experiment hapa (3ft × 2ft × 2ft) with 1 mm mesh net was used. Gold fish fry having a mean body weight of 0.007 g were used in all treatments. Fishes were fed at the rate of 10% of their body weight containing 34.11% protein. Water quality parameters were monitored at 10 days interval and the ranges were –temperature 24.75 to 27.75 oC, dissolved oxygen 3.68 to 4.09 mg/L, pH 7.3 to 8.16, ammonia 0.3 to 1 mg/L, nitrite 0.01 to 0.03 mg/L, phosphate 0.6 to 1 mg/L and alkalinity 119 to 187 mg/L. At the growth performances were evaluated by comparing mean final body weight, specific growth rate and food conversion ratio. The present study showed that the gold fish fry in T1 resulted the best mean final weight gain (1.188 g) followed by T2 (0.834 g) and T3 (0.686 g). The SGR ranged between 6.64 and 7.43% per day and FCR ranged between 3.56 and 4.12 with T1 showing the lowest FCR. The survival rate (%) ranged between 76.67% to 85.67%. From the present experiment it was found that individual fish growth rate was decreased with the increase of stocking density. Asian J. Med. Biol. Res. December 2017, 3(4): 504-515